Notificação de violência: prática dos profissionais da rede pública que atendem a mulher em situação de violência - Adriana Cristina Perini Ribeiro (2016)
Introduction: Violence in Brazil has been growing in recent years, creating a challenge for prevention and health promotion. Its a human rights violation that affects women in the entire world and in the most different aspects. The project To them, For them, For them, For us, from the Preventive Medicine and Social Department of Minas Gerais Federal University, through Distance Education (DE), trained health professionals and from others areas belonging to the attendance of woman in violence situations, nationally. Objective: The research objective was to study whether the professionals participants of the DEProject To them, who worked with woman in situation of violence realized the notification, if it was made available and the factors that influenced their achievement. Methodology: This is a cross-sectional study with a quantitative approach. A descriptive statistical analysis was made based on census obtained by the application of a structured questionnaire, answered by 466 participants during the registration in the DEsProject To them. The questionnaire was composed by 54 four questions, with 16 taken to be relevant to the research and make possible correlations. Results: For working time and the notification fulfillment relation, itprevailed those who worked more than three years (47%) on the attendance of women in situation of violence. About the availability of the notification form in the workplace and its filling, only 66,8% participants confirmed the realization of this action. The most participants (44,42%) had no difficulties to fulfill the form. However they expressed with the others, the factors that made it difficult, prevailing: the form is extensive, lacking time during the attending and understanding difficulties. Conclusion: Although the notification is provided in laws and normative acts, its clear that it hasnt been completely incorporated into the practical work of professionals who attend women in situation of violence.